13C isotopic signature and C concentration of soil density fractions illustrate reduced C allocation to subalpine grassland soil under high atmospheric N deposition. (October 2018) - Volk, Matthias; Bassin, Seraina; Lehmann, Moritz F.; Johnson, Mark G.; Andersen, Christian P.
Abstract: We followed soil C fluxes in a subalpine grassland system exposed to experimentally increased atmospheric N deposition for 7 years. Earlier we found that, different from the plant productivity response, the bulk soil C stock increase was highest at the medium, not the high N input as hypothesized. This implies that a smaller N-deposition rate has a greater potential to favor the biological greenhouse gas-sink. To help elucidate the mechanisms controlling those changes in SOC in response to N deposition, we produced four soil density fractions and analyzed soil organic C concentration [SOC], as well as δ 13 C signatures (δ 13 CSOC ) of SOC components. Soil respired CO2 (δ 13 CCO2 ) was analyzed to better distinguish seasonal short term dynamics from N-deposition effects and to identify the predominant substrate of soil respiration. Both at the start of the experiment and after 7 years we found a strong, negative correlation between [SOC] and δ 13 CSOC of the soil density fractions in the control treatment, consistent with an advanced stage of microbial processing of SOC in fractions of higher density. During the experiment the [SOC] increased in the two lighter density fractions, but decreased in the two heavier fractions, suggesting a possible priming effect that accelerated decomposition of formerly recalcitrant (heavy) organic matter pools. The seasonal pattern of soil δ 13 CCO2 was affected by weather and canopy development, and δ 13 CCO2 values for the different N treatment levels indicated that soil respiration originated primarily from the lightest density fractions. Surprisingly, [SOC] increases were significantly higher under medium N deposition in the <1.8 fraction and in bulk soil, compared to the high N treatment. Analogously, the depletion of δ 13 CSOC was significantly higher in the medium compared to the high N treatment in the three lighter fractions. Thus, medium N deposition favored the highest C sequestration potential, compared to the low N control and the high N treatment. Clearly, our results show that it is inappropriate to use plant productivity N response as an indicator for shifts in SOC content in grassland ecosystems. Here, isotopic techniques illustrated why atmospheric N deposition of 14 kg N ha −1 yr −1 is below, and 54 kg N ha −1 yr −1 is above a threshold that tips the balance between new, assimilative gains and respiratory losses towards a net loss of [SOC] for certain soil fractions in the subalpine grassland. Highlights: The SOC concentration and δ 13 C were strongly correlated across four density fractions. Co-occurring with a bulk soil C gain, SOC was lost in high density soil fractions. [SOC] was not determined by plant C production, but by the N-response of respiration. The net C balance, not the import of new C determined the δ 13 CSOC. δ 13 CCO2 reflected both seasonality of 13 C discrimination and the N deposition effect.